Effectiveness of Duloxetine in Treating Early Stage of Somatoform Disorder at Koshi Zonal Hospital - Pokhrel, Roshan; Rajbhandari, Nikeshmani; Sah, Shambhu; Kathet, Ragin; Sah, Prabhu; Karn, Shivam (Birat Journal of Health Sciences, 2019)
Introduction: Somatoform disorder (SD)is group of psychiatric disorders that disrupt multiple physical symptoms, accompanied by disturbance in thoughts, impairing activities of daily living due to muscle and joint pain, low back pain, headache, chronic tiredness, palpitation, stomach upset, dizziness and sleeplessness which may cause occupational and social dysfunction. Objective: Evaluation of patients by Numeric Pain Rating Scale (NPRS), Pain Disability Scale (PDS) and complications duloxetine medication during treating of patients with somatoform disorder at Koshi Zonal Hospital. Methodology: A total of 50 patients with first time diagnosis of SD were selected by in this cross sectional study on the basis of diagnostic and statistical manual (DSM-5), pain and other symptoms, were treated with Duloxetine medication in early stage of Somatoform Disorder and results were evaluated at 2nd week, 6th week and 12th week. The study was conducted from March 2016 to July 2017 at Koshi Zonal Hospital. Results: Out of 50 early SD patients, total mean age was 41.38 years (range 20-60), 21 patients recovered at 6th week and 22 patients recovered at 12th week but 7 patients needed other medications after 12 weeks. Duloxetine was well tolerated with nausea and headache being the most common complaint following use of duloxeting. Conclusion: Duloxetine can be both effective and well tolerated in the treatment of early stage of somatoform disorder.